Qualitative training aspects in middle distance running - Soulas, D.; Voutselas, V.; Papanikolaou, Z. (Journal of Human Movement Studies, 2005)
In the present study we aimed to evaluate the qualitative aspects of training that elite middle distance runners employ throughout their yearly training season to improve performance. Additionally we examined how their training methods correspond with the relevant research. We collected Information about the usage of interval training, continuous running, uphill running, and strength exercise during the weck throughout the seasonal training phases. Ten Spanish coaches, chosen according to their athletes' performance in International Events, took part in the present investigation. Interval running at 75-85% of VO2max and repeated running up to 85% of VO2max are mostly used in the build-up phases and less in the pre-competitive and competitive phases, whereas interval running at 85-95% of VO2max, repeated running above 85% of VO2max , and interval sprinting were mainly used in the pre-competitive followed by the competitive phase. Fartlek training and low and moderate intensity continuous running proved to be the most popular methods of continuous running throughout all the training phases, while high and low-high intensity running were mainly used during the pre-competitive and competitive phases. Continuous and interval uphill running is mostly used in the special phase and in a lesser amount in the basic and pre-competitive phases. Circuit training and resistance exercise are used mainly in build-up phases. Plyometrics and resistance running are used in a very small amount in all training phases. The training methods that elite runners employ to improve performance are mostly in line with research findings. However, in some cases recent suggestions, although proven to be efficient by research, seem to have no practical implementation.